Overcoming Students’ Academic Cheating in English E-learning Course (A Case Study of Teachers’ Effort at SMKN 6 Kendari) - Hanandita, Sisca Tiara; Nurnia, Nurnia; Mursalim, Mursalim (Universitas Halu Oleo, 2022)
This research aimed at finding the types of students' academic cheating found by the English teachers in e-learning at SMKN 6 Kendari and to finding the effort of English teachers to overcome students’ academic cheating in e-learning at SMKN 6 kendari. This research used descriptive qualitative research design and used case study research method. The subject in this research were three English teachers at SMKN 6 kendari. The instruments of this research were the researcher as a human instrument, an interview guide, and documentation. Techniques of data collection in this research were deep interviews and document review. The results of this research show that; types of students’ academic cheating that English teachers found in e-learning were plagiarism, wrong cooperation, and cheating during the exam. The efforts made by the English teacher in overcoming student academic cheating in e-learning were giving warnings to students, giving motivation, limiting the time, and changing the questions.